Uji Keseragaman Bobot Racikan Pulveres pada Pasien Anak di Puskesmas Daerah Kota Mataram - Yosi Agsanita (Unram Medical Journal, 2021)
Background : Weight uniformity becomes a determining factor in therapeutic success, which indicates the accuracy of drug dosage. One of the disadvantages of distributing divided powders preparations by the visual method is the non-uniformity of weight. Divided powders are still prescribed for pediatric patients. The slight change in dosage can caused different effects in pediatric patients. Objective : The purpose of this study was to determine the weight uniformity of divided powders in prescribing pediatric patients at 10 public health centers in Mataram. Method : This study was a descriptive research with a cross-sectional design. The sampling method used was non-probability sampling with a saturated sampling technique. The weight uniformity standard of divided powders follows Farmakope Indonesia III guidelines. Microsoft Excel 2010 software was used to analyze the data. Results : The maximum standard deviation of each 30 divided powders prepared in the morning and the afternoon were 107.75% and 70.17%, respectively. Conclusion : All divided powders tested do not fulfill the requirements in the weight uniformity of divided powders according to the Farmakope Indonesia III standard because they had >15% of deviation.